Interopérabilité des bases de données scientifiques : une sobriété de façade - Régis Witz; Guillaume Porte (Humanités Numériques, 2025)
Any task is more sustainable if it consumes fewer resources, over its entire lifecycle. Some of the challenges of Digital Humanities are tasks related to interoperability between databases, such as documentation, alignment, migration and publication. Often requiring specialised knowledge, these tasks can quickly become time-consuming. After recalling the context in which these tasks are generally undertaken, this article will propose solutions for reducing their consumption of resources, of human resources in particular. Finally, it will discuss the benefits and limitations of these solutions.